(untitled) (Global Journal of Management and Business Research, 2023)
This paper identifies various attributes influencing consumers to purchase Icecream from a retail store Our team has done this research during the year 2021 Notably it confesses the behavioural patterns of consumers and perceptions regarding ice cream with the association between the income effect and purchase decisions To conduct the research we collected raw data from an online survey of 152 consumers of different ages Participants from the separate age group provided their opinion in the pre-setted questionary After gathering the raw data we used three effective methods Henry Garrett s ranking technique Chi-Square Independence Test and PCA to rank the consumer-preferred ice cream flavour income effect on purchasing ice cream and factors that attract consumers to buy ice cream Raw data was gathered from the survey and coordinated with the Excel Programme SPSS was used to implement Chi-Square and PCA tests but Henry Garret s ranking was done on Excel Programme This step-by-step analysis shows the consumer inside regarding existing brand preferences regarding ice cream in Bangladesh Furthermore this research depicts the scenario of the Dhaka city dwellers about their choosing factors for ice cream favourite flavours and purchase power